The Effect of Diabetes on Canadian Labour Market Performance - Wang, Liang (Université d'Ottawa | University of Ottawa, 2010)
This study examines the impact of diabetes on the employment and personal income of Canadian males and females aged 30-64. Using data from the Canadian Community Health Survey (2007-2008), I use three versions for the diabetes variable (diabetes status, T